Indirect effect of nutrient accumulation intensified toxicity risk of metals in sediments from urban river network - Wei, Yuquan; Zhang, Hao; Yuan, Ying; Zhao, Yingshuang; Li, Guanghe; Zhang, Fang (Environmental science and pollution research international, 2020)
The levels of metals in sediments of urban river ecosystems are crucial for aquatic environmental health and pollution assessment. Yet little is known about the interaction of nutrients with metals for environmental risks under contamination accumulation. Here, we combined hierarchical cluster, correlation, and principal component analysis with structural equation model (SEM) to investigate the pollution level, source, toxicity risk, and interaction associated with metals and nutrients in the sediments of a river network in a city area of East China. The results showed that the pollution associated with metals in sediments was rated as moderate degree of contamination load and medium-high toxicity risk in the middle and downstream of urban rivers based on contamination factor, pollution load index, and environmental toxicity quotient. The concentration of mercury (Hg) and zinc (Zn) showed a significant correlation with toxic risks, which had more contribution to toxicity than other metals in the study area. Organic nitrogen and organic pollution index showed heavily polluted sediments in south of the study area. Though correlation analysis indicated that nutrients and metals had different input zones from anthropogenic sources in the urban river network, SEM suggested that nutrient accumulation indirectly intensified toxicity risk of metals by 13.6% in sediments. Therefore, we suggested the combined consideration of metal toxicity risk with nutrient accumulation, which may provide a comprehensive understanding to identify sediment pollution. Graphical abstract Toxicity rate of metals in sediments from urban river network indirectly intensified by nutrients accumulation